2017
DOI: 10.1002/pola.28897
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic poly(benzyl ether)‐b‐poly(N‐vinylcaprolactam) block copolymers: Self‐organization in aqueous media, thermoresponsiveness and biocompatibility

Abstract: Four generations of new amphiphilic thermoresponsive linear‐dendritic block copolymers (LDBCs) with a linear poly(N‐vinylcaprolactam) (PNVCL) block and a dendritic poly(benzyl ether) block are synthesized by atom transfer radical polymerization (ATRP) of N‐vinylcaprolactam (NVCL) using dendritic poly(benzyl ether) chlorides as initiators. The copolymers have been characterized by 1H NMR, FTIR, and GPC showing controlled molecular weight and narrow molecular weight distribution (PDI ≤ 1.25). Their self‐organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…However, the molecular weights from gel permeation chromatography (GPC) have a significant difference between the M n,NMR values and M n, theo values. This result may be attributed to the difference in hydrodynamic volume of the copolymers and the linear PS standards used for calibration 27,38 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the molecular weights from gel permeation chromatography (GPC) have a significant difference between the M n,NMR values and M n, theo values. This result may be attributed to the difference in hydrodynamic volume of the copolymers and the linear PS standards used for calibration 27,38 …”
Section: Resultsmentioning
confidence: 99%
“…Although the lower critical solution temperature (LCST) of PNVCL is close to LCST of poly( N ‐isopropylacrylamide) (PNIPAM), the most representative thermoresponsive polymer, there are significant differences in the thermodynamic and molecular mechanisms underlying the phase transition 25,26 . In comparison with PNIPAM, PNVCL has some obvious advantages, such as lower interaction with biomolecules and no tendency to crystallize 27 . The 2, 2′‐dimethylolpropionic acid (bis‐MPA) molecule, comprising two hydroxyl groups and one carboxylic group, has successfully been developed for the construction of dendritic materials, such as monodisperse dendrons and dendrimers or polydisperse hyperbranched polymers and linear‐dendritic hybrids.…”
Section: Introductionmentioning
confidence: 99%
“…(B)—in D 2 O; the other 1 H NMR spectra in D 2 O can be found in Supporting Information, SM1–2]. The aggregates therefore comprise a hydrophobic PLA core and a hydrophilic polyether shell, as the mobility of the internal PLA segments is restricted by the formation of the core–shell structure in the aqueous medium . From 2D DOSY NMR, the diffusion coefficient at 25 °C in D 2 O of 5.8 × 10 −11 m 2 s −1 was calculated for PEO signal in PLA 6 –PEO 8 –PLA 6 copolymer (Supporting Information, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…While a majority of studies reported to date have utilized PEG-based polymers as the hydrophilic segment, a few studies have also focused on utilization of other hydrophilic polymers. Recently, Bi and coworkers reported thermoresponsive micellar aggregates prepared from diblock constructs composed of poly(benzyl ether) dendrons and linear poly( N -vinylcaprolactam) [ 77 ]. Dendritic poly(benzyl ether) blocks containing a benzyl chloride group at their focal point were used as initiators for atom transfer radical polymerization of N -vinylcaprolactam.…”
Section: Nano-sized Aggregates From Polymer-dendron Diblock Conjugmentioning
confidence: 99%